Programa de formação de professores: ênfase no ensino de avaliação de preferências das crianças com transtornos do espectro do autismo - Bezerra, André Barbosa (2017)
From the discovery of Kanner (1943) in relation to the disorder of the spectrum of autism, there is a clear concern regarding the treatment of people with this disorder. The educational literature that guides the teaching procedures based on Applied Behavior Analysis is based on evidence. There are records of research in the last thirty (30) years that demonstrate the effectiveness of education in the treatment of people with autism spectrum disorder. These results further evidence the need to invest in teacher training that covers procedures based on concepts and principles of Applied Behavior Analysis. In this sense, the present study aimed to develop and apply a teaching program for future teachers so that they learn to apply preference evaluations, since the success of educational interventions requires the use of effective reinforcers. Four students from the Pedagogy course of the Federal University of Alagoas participated in the study. Initially, participants were asked to demonstrate how they would apply a preference assessment using three different models (single stimulus, forced choice and multiple stimuli) in role-play sessions; The performance of the participants was then calculated; Then theoretical expositions on three procedures were performed to assess the preferences of children with this disorder. After the theoretical presentation, participants were again asked to demonstrate how they would apply these three procedures. They were then taught to apply the three procedures in role-play sessions. At these sessions, the researcher provided feedback for the correct and incorrect responses from participants. The role-play sessions were carried out between the participants until reaching the criterion of learning. After reaching the criterion, the participants were evaluated again, with the first participant reaching 100% in the application of single stimulus preference, 100% in forced choice and 97.25% in multiple stimulus; In turn the second reached respectively 95%, 100% and 100%; In this, the third reached 100%, 100% and 100%; And the room reached 100%, 100% and 88%. This teacher training program provided an effective model for training practitioners working directly with children with autism spectrum disorder, since average participants increased their performance in applying the preference assessments by 80.45%.